Traçando destinos, entrecruzando territórios: sociabilidade dos redeiros de Patos-PB - Souza, Maria Rodrigues de (2004)
In this work I analyse forms of sociability among hammock sellers from Patos, PB, including living experiences with their marital partners, using the methodology of interviews and the direct observation of aspects of their daily lives. The theoretical perspective has as main founts: (1) contributions done by Marcel Mauss on the theme of sociability nets, which are built around structures of giving and reciprocity; (2) the contributions done by Bourdieu on the theme of honour among the Kabila; (3) the contributions done by Simmel, with his discussion on sociability forms. In order to understand the social organisation of hammock sellers and theirs wives in the context of hammocks and other sales and other craft-works sales, I used the ethnographic method and did semi-structured interviews. Besides it I made direct observation and participated in informal chats between hammock sellers I chose, in order to have some life stories. Among the main outcomes of my research I bring out the following: (1) the honour of the hammock sellers from Patos-PB is built with reference to the debt logic; (2) the sociability of hammock sellers is determined by the imposed reciprocity of debt, which helps them in building and make strong social links; (3) the hammock sellers honour expresses itself in varied forms according to the different places in which hammock sellers circulate. It varies as well as a function of social roles they play at the community.